Preexisting hemodialysis and survival outcome in out-of-hospital cardiac arrest patients: Ulsan, South Korea - Song Yi Park; Sun Hyu Kim; Sun Hyu Kim; Byungho Choi; Byungho Choi (Frontiers in Medicine)
BackgroundAlthough the incidence of sudden cardiac death is higher in hemodialysis (HD) patients, whether out-of-hospital cardiac arrest (OHCA) survival outcomes are poorer in this group remains unclear. This study aimed to assess the impact of HD on survival outcomes among adult nontraumatic OHCA patients and to compare these outcomes between HD and non-HD groups.MethodsThis observational cohort study retrospectively analyzed data from adult nontraumatic OHCA patients in Ulsan, South Korea, from January 2017 through December 2022. Multivariable logistic regression analysis was applied to evaluate whether HD was a risk factor for survival in OHCA patients. Survival was compared between the two groups in unadjusted, balanced groups by propensity score matching (PSM) and inverse probability of the treatment weighting (IPWT).ResultsThe study included 2,489 patients (64 HD group and 2,425 non-HD group). Undergoing HD was not significantly associated with any return of spontaneous circulation (ROSC) (adjusted odds ratio [95% confidence interval], p-value, 1.648 [0.934–2.907], 0.085), survival to discharge (1.544 [0.734–3.250], 0.252), or neurological outcomes (0.394 [0.017–9.346], 0.564). There were also no significant differences observed in any ROSC (1.648 [0.934–2.907], 0.085), survival to discharge (1.544 [0.734–3.250], 0.252), or favorable neurological outcome (0.394 [0.017–9.346], 0.564) between the two unadjusted groups. The insignificant survival differences were persistently observed in the PSM group and IPWT group.ConclusionAlthough HD may pose a risk factor for cardiac arrest, our study did not find a significant association with survival outcomes in OHCA patients. Additionally, no notable survival difference was observed between HD and non-HD groups. Therefore, resuscitation efforts in HD patients should not be underestimated.